The Japanese Version of the Daily Record of Severity of Problems for Premenstrual Symptoms: Reliability and Validity Among the General Japanese Population - Takeda T; Yoshimi K; Kai S; Inoue F (International Journal of Women's Health, 2024)
Takashi Takeda, Kana Yoshimi, Sayaka Kai, Fumi Inoue Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, Osaka-Sayama, Osaka, JapanCorrespondence: Takashi Takeda, Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, 377-2 Ohno-Higashi, Osaka-Sayama, Osaka, 589-8511, Japan, Tel +81-72-366-0221 (Ext. 3393), Fax +81-72-366-6661, Email take@med.kindai.ac.jpPurpose: The validity and reliability of the Japanese version of the Daily Record of Severity of Problems (DRSP-J) have already been confirmed in a population with premenstrual symptoms. This study aimed to assess the validity and reliability of the DRSP-J in the general population.Patients and Methods: We analyzed data from 113 Japanese women with regular menstrual cycles who applied to participate in an ongoing study. Participants were recruited regardless of the severity of premenstrual symptoms, and their menstrual cycles were monitored using the DRSP-J for two cycles. Reliability was examined using Cronbach’s α, a measure of internal consistency, and test-retest reliability. Structural validity was assessed using a principal component analysis (PCA). The Hospital Anxiety and Depression Scale (HADS) and EuroQol-5 Dimensions-5 Levels (EQ-5D-5L) were used to examine concurrent validity. The agreement between the clinical diagnoses based on the diagnostic criteria for premenstrual syndrome/premenstrual dysphoric disorder and that based on the DRSP-J score was examined using the kappa coefficient.Results: Cronbach’s α for DRSP-J total score was 0.96. The DRSP-J total score showed high test-retest reliability. The PCA showed a two-factor model describing “Mood” and “Behavior/Physical” symptoms. The DRSP-J total score was highly correlated with the HADS total and EQ-5D-5L scores. The classification of “moderate to severe premenstrual syndrome” and “premenstrual dysphoric disorder” by clinical methods and the criteria based on the DRSP-J were in good agreement (kappa values = 0.78).Conclusion: The DRSP-J is a reliable and valid measure of premenstrual symptoms in the general Japanese population, including those with few or no symptoms.Keywords: premenstrual syndrome, premenstrual dysphoric disorder, psychometric testing, premenstrual symptom